The impact of exercise on cardiovascular system: Molecular signaling pathway and cardiac adaptations - Bauyrzhan Toktarbay; Zaukiya Khamitova; Nurmakhan Zholshybek; Dinara Jumadilova; Yeltay Rakhmanov; Makhabbat Bekbossynova; Abduzhappar Gaipov; Alessandro Salustri (National Scientific Medical Center, 2023)
The purpose of this review is to describe the impact of endurance and strength physical training on the cardiovascular system by reviewing the molecular signaling pathways, which plays a key role in different muscle adaptations, and the cardiac changes in terms of metabolic and cardiac remodeling, and hemodynamics. In response to endurance-exercise, multiple signaling pathways, including Ca2+-dependent pathways, reactive oxygen species (ROS), AMP-dependent protein kinase (AMPK), and mitogen activated protein kinases (p38 MAPK), are involved in the regulation of peroxisome-proliferator-activated receptor-γ coactivator-1α (PGC-1α), which controls the mitochondrial biogenesis. Strength training increases the insulin-like growth factor (IGF-1) which initiates the phosphatidylinositol 3-kinase (PI3-k)-(AKT)-(mTOR) signaling cascade, resulting in the synthesis of proteins and the muscle hypertrophy. In addition to the well-documented changes in skeletal muscle, a critical component of the response to exercise training is the dynamic cardiac remodeling, which is classified as either pathological or physiological depending on triggers.